Hendrix : the ultimate illustrated history - Gaar, Gillian G., 1959-; Hunter, Dave, 1962-; Kubernik, Harvey, 1951-; Salewicz, Chris; Uhelszki, Jaan (Voyageur Press, 2017)
The only definitive illustrated bio of the man widely considered the greatest rock guitarist of all time-published on the eve of what would have been his 75th birthday.